FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN MEMBELI IKAN KEMBUNG DI PASAR BERINGHARJO, YOGYAKARTA - Veronica Vony Rorong; Budiarto Budiarto; Siti Syamsiar (Jurnal Dinamika Sosial Ekonomi, 2017)
This study is aimed toanalyze the influence of cultural factors, reference groups, economic conditions as well as consumer knowledge on deciding to buy mackerel fish at Bringharjo Market Yogyakarta. This is also to identify consumer knowledge on formalinto conserve mackerel fish. The method usedin this research is descriptive which is based on the results of survey and interview with primary and secondary sources of data types. The research area is determined purposively. The main criteriato determine Bringharjo marketas location research is the fact that Bringharjo is the largest market that has the high est number of fish trading. The analysis model used here is linear regression analysis logic model. The results have shown that the variables of culture, economy and knowledge influence consumers decisions to buy mackerel fish at Bringharjo Marker.  Keywords: mackerel fish, consumer decisions